Stress and deformation of optimally shaped silicon microneedles for transdermal drug delivery - Zainal Abidin, Hafzaliza Erny; Poh, Choon Ooi; Teck, Yaw Tiong; Marsi, Noraini; Ismardi, Abrar; Mohd Noor, Mimiwaty; Nik Zaini Fathi, Nik Amni Fathi; Abd Aziz, Norazreen; Sahari, Siti Kudnie; Sugandi, Gandi; Yunas, Jumril; Chang, Fu Dee; et al. (Elsevier, 2020)
In this study, we demonstrated the fabrication of the concave conic shape microneedle with the aid of COMSOL Multiphysics simulation. The stress and buckling of the microneedle structure were simulated by applying various loads ranging from 50 to 800 g perpendiculars to the tip in order to predict the occurrence of microneedles structure deformation. The simulation study indicated that the surface buckling deformation does not occur to the microneedle structure with the increment of the load. The microneedles with dimensions of height and diameter tip ranging from 60 to 100 μm and 1 to 4 μm, respectively had been fabricated via an etching process in a mixture of hydrofluoric acid, nitric acid, and acetic acid. Three optimized microneedles but different in the structures were fabricated via the acidic etching process. The reproducibility of three different microneedle structures was 15, 20, and 60%, respectively. Stress and buckling analyses of the fabricated microneedles were further carried out on the rat skin. The obtained experimental results show promising applications for the deep dermis, stratum corneum to epidermis layer penetration.